2016
DOI: 10.1111/jocd.12295
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of a novel nutritional and phytonutrient blend on ultraviolet radiation‐induced skin damage and inflammatory response through aging defense mechanisms

Abstract: Eight weeks of oral supplementation positively impacted ADMs resulting in protection against UVR-induced skin damage and improvements in facial skin attributes and characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In their 1‐year follow‐up of 21 CRSr patients who underwent FESS, they noted recovery of sinus mucosa ultrastructure, including mucociliary clearance in patients after FESS. Gray et al posited that CRSr patients who have also undergone surgical resection for malignancy are likely to have abnormal sinonasal anatomy in addition to fibrosis and synechiae that may predispose to delayed healing . A third study of 10 nasopharyngeal carcinoma patients with CRSr showed that FESS procedures serve as an effective treatment for patients with improved quality of life seen in patients 2 years from surgery …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their 1‐year follow‐up of 21 CRSr patients who underwent FESS, they noted recovery of sinus mucosa ultrastructure, including mucociliary clearance in patients after FESS. Gray et al posited that CRSr patients who have also undergone surgical resection for malignancy are likely to have abnormal sinonasal anatomy in addition to fibrosis and synechiae that may predispose to delayed healing . A third study of 10 nasopharyngeal carcinoma patients with CRSr showed that FESS procedures serve as an effective treatment for patients with improved quality of life seen in patients 2 years from surgery …”
Section: Discussionmentioning
confidence: 99%
“…CRS is a common side effect of radiation therapy studied most extensively in patients after treatment of nasopharyngeal carcinoma, during which side effects of surgery, chemotherapy, and radiation are thought to disrupt the sinonasal cavity and lead to sinonasal symptoms . The pathophysiologic mechanism of radiation‐induced CRS (CRSr) has been attributed to radiation‐induced damage of ciliary motility and mucus‐secreting cells . The effects of radiation therapy may also depend on extrasinus factors, such as dose administered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in establishing the doses for the C. elegans study, no toxic levels of the supplement were identified (see methods). Furthermore, the safety as well as the efficacy of this mixture for other biomarkers of health has been tested and confirmed in humans [7], but experiments investigating the possibility that this CR mimetic may be useful to increase the healthspan long-term in humans remains a longer-term goal.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the micronutrient blend has been previously published [7] the blend is composed of: ultra-pure fish oil concentrate standardized to eicosapentaenoic acid (EPA) and decosahexanoic acid (DHA), resveratrol (from Polygonum cuspidatum root), quercetin (from Dimorphandra mollis fruit extract), purple corn (Zea mays L.) cob extract, rosemary (Rosmarinus officinalis L.) leaf extract, citrus bioflavonoids (naringin and hesperidin), coenzyme Q 10 , alpha lipoic acid, astaxanthin (a carotenoid from Haematococcus pluvialis algae), lycopene (a carotenoid), lutein (a carotenoid from Marigold flower (Targetes erecta), vitamin D 3 (as cholecalciferol), vitamin K 2 (as menaquinone-7) and d-limonene (from citrus sinensis peel oil); doses are described in Table 1.…”
Section: Micronutrient Blendmentioning
confidence: 99%